Glamour photography - Esterhuizen, Robert (Bloemfontein: Central University of Technology, Free State, 1995)
Beauty photography has often been considered to be a photographi c direction with only a si ngle dimension namely a pretty face on a photograph. The truth of the ~atter is actually not that simple. In this dissertion the researcher will show that beauty photography cons ists of numerous facets. The reader will have a chance to come face to face with the challenges that meets the beauty photographer . We will not only discuss problems the photographer might experience but the researcher will also provide solutions. The aim of this dissertation will no t only be to inform the reader but even more important to create a better understanding of the concept "Beauty photography." An integral part of any photographer's success is marketing and selling himself and his product . The researcher will show in what sense marketing and selling himself is essential for Beauty Photography. There will be personal inserts by the researcher of photos taken by himse lf. With these inserts the researcher wi ll show and explain how beauty photography can be connected to various other photographic directions on the following aspects of each photograph: * * * * lighting Make-up Models Props The researcher will give a -definition and short overview of the BEAUTY concept . This chapter will consist of five headings and several sub-headings. The five headings will read as follows: 1. Beauty and glamour portraiture 2. Making beauty with cosmetics 3. Lighting the nude 4. Beauty in the studio 5. Pretty women Any successful business must have a successful marketing strategy. This dissertation will investigate different methods that can be applied to create a successfull marketing strategy in terms of beauty photography. Not only is proper marketing essential for a business but it also helps with another important factor, selling yourself. This dissertation will show how to sell yourself as a beauty photographer. Without light, photography would be a mere vision of mind. No wonder that ligh t plays such an important role in photography. With the correct lighting techniques you can create not only correctly exposed images but one can also produce wondrous special effects. The researcher will investigate lighting techniques ~nder the following headings: 1. Lighting the glamour portrait 2. Lighting the nude The terms beauty photography can cover such a wide range of subjects that one cannot cover all of them in detail . That is why the researcher will cover three categories which includes glamour portraiture , nudes and fashion . This chapter will include personal inserts with elaborations on these personal inserts. PORTRAITS * * * Portraits will be shot on a medium format camera as well as 35mm cameras An important ingredient of the researcher's portraits will include the use of colour Another important characterist ic is the way the photos are cropped, only the very essentia l are left, in other words the model's most striking features
Thesis
Keywords: Photography of women; Glamour photography; Photography of the nude; Photography - Study and teaching - South Africa